Léxico político latino del reino de León (s. VIII-1230): 'consul' y 'proconsul' - Pérez Rodríguez, Estrella (2013)
This paper studies the use of two political terms from classical latin : consul and proconsul (as well as the derivatives consularis and consulatus), inside the textual corpus of the kingdom of León (8th century-1230), where they have developed new meanings. By means of a detailed analysis of the texts, the author proves that, in the charters, both of them mean «count» (and are synonyms of comes) and, in some chronicles, they have also the meaning of «governor» , and that they are used with a stylistic aim so that the texts gain a more classic and learned status.
Cet article discute l’usage de deux mots provenant du latin classique, consul et proconsul(ainsi que leur dérivés consularis et consulatus), dans le corpus des textes du royaume d’Asturies et Léon (VIIIe siècle -a. 1230). A cette époque, bien qu’ils désignent encore des offices politiques, leur signification a évidemment changé. L’analyse des témoins permet de reconnaître que dans les diplômes ils signifient tous les deux «comte» (et sont synonymes de comes) et dans quelques chroniques aussi «préfet» , et qu’ils sont employés avec un but stylistique pour donner aux textes un caractère plus classique et érudit.
Keywords: Lexicografía; Política; Lengua latina